A prospective study on outcome of function after proximal row carpectomy - Gadi, Chaitanya; Venugopal, S. M.; Kumar, Bhaskaranand; Gudaru, Karthik (International Journal of Research in Orthopaedics, 2019)
Background: Proximal row carpectomy (PRC) is a procedure with varied indications. The purpose of this study was to evaluate functional outcomes with PRC in wrist flexion deformities, neuromuscular disorders and also post-traumatic wrist arthritis. Methods: A prospective study was performed on all patients who underwent PRC between April 2015 and December 2017, in BIRRD (T) hospital, Tirupati, Andhra Pradesh with a minimum follow up of 6 months. Outcome was assessed in terms of range of motion (ROM), grip strength, quick disabilities of the arm, shoulder, and hand (QDASH) score and pain score. Data was analyzed using the Student t-test. Results: Thirty-two patients underwent PRC of which 12 are neuromuscular disorders, 10 are wrist flexion deformities, 10 are post-traumatic wrist arthritis. On the final follow-up, significant improvement in ROM was observed in wrist flexion deformities and neuromuscular disorders, whereas grip strength and QDASH scores showed a significant difference in post-traumatic wrist arthritis. Pain was studied only in post-traumatic wrist arthritis, all were very much pleased with pain reduction. Conclusions: PRC is fairly a reliable procedure for all the indications in our study. We consider that PRC is a promising procedure in correcting wrist flexion deformities. Though there has been significant improvement in all the parameters for all the cases, we consider this procedure is best suited for post-traumatic arthritis group.